Pembuatan dan Uji Impact Plat dari Serat Karbon Kevlar - Lewi Gonzales Marpaung; Dadan Ramdan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Carbon fiber has been widely used in various fields thanks to its superior properties in terms of stiffness, lightness, strength and corrosion resistance. This study uses an experimental method using a mold and a vacuum machine and tested using a charpy impact. This test aims to determine the strength properties of a plate made of carbon fiber type Kevlar blue reflective metallic plain 200 gm formed into a plate. The results of the plate test using 3 layers of carbon fiber have an impact strength of 327 (Joules), a 7-layer plate has an impact strength of 654 (Joules), and an 11-layer plate has an impact strength of 752 (Joules). The process of making the plate by infusion, so that it can affect the density of each layer, and can be formed into a plate. The impact test was carried out to determine the impact strength value of the designed plate. From the results of the impact test, the 11-layer plate can be applied to the car body